Sundanese Translations of the Qur’an in West Java: Characteristics and the Limits of Translation - Rohmana, Jajang A (IAIN Surakarta, 2019)
There is no target language can fully represent the source language. This study focuses on the problem of differences, uniqueness and limitations of Sundanese as the target language in accommodating Arabic Quran, using the linguistic approach to translation. I use eleven translations of the Quranic Sundanese asthe mainobject. This study shows that there is a similar structure of Sundanese language in the midst of variations of the translation of the Quran. I confirm that the translation of the Quran in Sundanese has limitations and barriers,such as thechange of lexical, word types and unit of semantic and structure of sentences. The most complicated is translation in the form of Sundanese metrical verse or dangding. The translationsof the Quran in Sundanese, unlike the Bible translationsin Christianity, tend to be fettered by the structure of source language.The Sundanese translators generally difficultto use the structure of target language, because it is bounded by their loyaltiesto the source language. Therefore, there are various compromises were taken by translators to bridge the complexity between both target and source language structures. It is an attempt to show inability of Sundaneselanguage to accommodate Arabiclanguage in the midst of rich and complexity of the language